Exploring the Link between Obesity and Hypothyroidism: Obesity and Hypothyroidism - Khan, Salman; Rehman, Abdur; Zubair, Muhammad; Shah, Naseeb ur Rehman; Khan, Nisar (Pakistan Journal of Health Sciences, 2024)
The association between obesity and hypothyroidism has garnered significant attention due to their overlapping prevalence and potential bidirectional relationship. Objectives: To investigate the link between obesity and hypothyroidism in local population of Pakistan. Methods: A cross-sectional study conducted at Medical Unit DHQ Teaching Hospital in Dera Ismail Khan from 2022 to 2023 involved 550 participants. Demographic characteristics, age, gender, clinical parameters, body mass index (BMI), comorbidities, and thyroid blood tests (TSH, T4) were collected through systematically designed questionnaire. Lifestyle factors, dietary habits, physical activity and medication history were also recorded. Electronic medical records were reviewed to collect demographic information and medication history. Results: Data from 550 participants, meeting inclusion/ exclusion criteria, showed that individuals with hypothyroidism had a lower mean age (42.5 ± 8.6 years) than obese counterparts without hypothyroidism (45.2 ± 9.8 years). The odds ratio (OR) for the association between obesity and hypothyroidism was 2.45 (95% CI: 1.75 - 3.42), indicating a significant positive correlation (p < 0.001). Family history of thyroid disorders was present in 24.0% of individuals with subclinical hypothyroidism and 20.5% without. Mean BMI was higher in individuals with subclinical hypothyroidism (29.3 ± 3.5 kg/m2) than those without (27.8 ± 2.9 kg/m2). Conclusions: Our study confirmed obesity’s strong link to hypothyroidism, especially in females, stressing the need for thyroid evaluation in obese individuals, particularly in clinical settings